UPM is sixth best in GreenMetric ranking - New Straits Times,
KUALA LUMPUR: Universiti Putra Malaysia added another feather to its cap by clinching sixth place in the GreenMetric world University Ranking 2010 organised by Universitas Indonesia recently.UPM said it not only finished sixth best in the world among 95 countries that participated in the ranking list,but also emerged as the best in Asia,based on its extensive promotion of green technology. "The recognition shows the commitment of UPM to ensure the greening of the campuses and implementation of green-based technology within its campus,"said the statement. the University of california,United States,emerged as the top- listed university while the University of Nottingham,University,Canada,finished second and third respectively.-Bernama